HIV Infection and the Abnormal Cervical Cytology - Chayachinda, Chenchit; Jirattigalachote, Apiradee; Chuenchoo, Sivakorn; Poorichitiporn, Arnon; Thamkhantho, Manopchai (Thai Journal of Obstetrics and Gynaecology, 2019)
Human immunodeficiency virus (HIV) infection has been known as a chronic, immunocompromising condition, which accelerates the natural history of many diseases, including cervical cancer. As known, human papillomavirus (HPV) is the principal etiologic cause and its persistent infection can transform normal cervical cells to cancers. HPV and HIV possibly co-facilitate the transmission of each other. In addition, the co-existence of oncogenic and non-oncogenic HPV appears very common. In 2018, the recommendations provided by the Panel on Opportunistic Infections in HIV-Infected Adults and Adolescents for screening cervical cancer in HIV-infected women were launched. In contrast to the previous guideline by the Center for Disease Control and Prevention (2009) which showed that the screening interval was one year once the first three Pap tests were negative, that in the recent recommendations is three years. Moreover, new techniques such as co-testing are taken into consideration. The article aims to share our experience at the Siriraj Female Sexually transmitted Diseases Clinic, Siriraj Hospital, which has been taking care of this special group of population for nearly two decades.